MCSFilter performance: a comparison study - Luis, Monteiro (2022)
Optimization plays an important role in an industrial context, generating considerable savings [1,2]. There are several optimization algorithms available. This work focuses on the MCSFilter, a multilocal optimization method able to obtain local and global minimizers — a multistart strategy coupled with a local coordinate search filter to deal with all the constraints [3,4,5].